DEVELOPMENT OF MACROMEDIA FLASH MODULE IN THE LEARNING MEDIA COURSE FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITY OF PEJUANG REPUBLIK INDONESIA: PENGEMBANGAN MODUL MAKROMEDIA FLASH PADA MATA KULIAH MEDIA PEMBELAJARAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS PEJUANG REPUBLIK INDONESIA - Kurniati, Ratnah; Ramly, Rizal Arizaldy (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
Students in the Faculty of Teacher Training and Education, University of Pejuang Republik Indonesia, comes from different background and knowledge. The problem is when the lecturer teaches the students to use an application on the computer, in this case the macromedia flash application. This research aims to develop a macromedia flash module that can be used by the students in the Faculty of Teacher Training and Education, University of Pejuang Republik Indonesia, as well as to determine the need, design, level of validity, practicality, and effectiveness of the Macromedia flash module. Furthermore, to distribute the module. In this study, the researcher uses research and development (R&D) methods with a 4-D development model, define, design, develop and disseminate. The developed module is then tested for its feasibility with validity, testing, and product evaluation. The results of this research showed that the level of validity coefficient by the two validators with an average score of 75%, with the level of practicality after being given a limited trial to students getting a very practical category with an average score of 3.32% and the level of effectiveness of the Macromedia flash module could be seen through pre-test and post-test with an average score of 56.00% during the pre-test and 89.20% during the post-test. In conclusion, the macromedia flash module can help lecturers and students to make the learning process more effective.